A State-of-the-Art Review on the Incorporation of Recycled Concrete Aggregates in Geopolymer Concrete - Bahareh Nikmehr; Riyadh Al-Ameri (Recycling, 2022)
Geopolymer concrete (GC) has the potential to incorporate recycled concrete aggregates (RCA) obtained from construction and demolition waste. This research aims to review the current state-of-the-art knowledge of the RCA in GC and identify the existing knowledge gaps for future research direction. This paper highlights the essential factors that impact the GC’s mechanical and durability properties. Moreover, the influence of various percentages of coarse and fine RCA and the pattern of their replacement will be assessed. The effect of aluminosilicate material, alkaline activators, and curing regime also will be evaluated. Besides, the durability-related characteristics of this concrete will be analysed. The impact of exposure to a higher temperature, freeze–thaw cycles, marine environment, and acid and alkali attack will be comprehensively reviewed. A literature review revealed that increasing alumina silicate content, such as slag and metakaolin, and increasing the Na2SiO3/NaOH ratio and alkali-activator-to-binder ratio improve the hardened GC. However, increasing slag and metakaolin content and the Na2SiO3/NaOH ratio has an adverse impact on its workability. Therefore, finding the optimum mix design for using RCA in GC is vital. Moreover, there is a scope for developing a self-compacting GC cured at ambient temperature using RCA.